Literature, language, and multiculturalism in Scandinavia and the Low Countries - Behschnitt, Wolfgang; Mul, Sarah de; Minnaard, Liesbeth (Text (Rodopi (Firm)), 2013)
"This book not only offers a comprehensive theoretical and methodological analysis of multilingualism and multicultural literature, but also provides overviews sketching the discourse on multiculturalism, language and the development of the literary field in Sweden, Denmark, the Netherlands, and Flanders. Besides it presents a broad range of in-depth analyses of selected literary texts from each of these countries"--Page 4 of cover